Realizing consumers’ existential dreams via product marketing and mixed reality: a perspective based on affective neuroscience theories - Yin, Bin; Jiang, Yan-Bin; Chen, Jian (Frontiers in Neuroscience, 2023)
In an era of swift societal changes and escalating consumerism, this paper presents an exploration of an innovative approach that integrates product marketing strategies, mixed reality (MR) technology, and affective neuroscience theories to actualize consumers’ existential dreams. MR, with its unique capacity to blend the virtual and real worlds, can enhance the consumer experience by creating immersive, personalized environments that resonate with consumers’ existential aspirations. Insights from affective neuroscience, specifically the brain’s processing of emotions, guide the development of emotionally engaging marketing strategies, which strengthen the connection between consumers, products, and brands. These integrated strategies not only present a novel blueprint for companies to deepen consumer engagement but also promise more fulfilling and meaningful consumer experiences. Moreover, this approach contributes to societal well-being and prosperity, marking a significant stride in the field of marketing.